Facial Recognition & Fingerprint Based Authentication System for Industry 4.0 Cybersecurity - Enriquez Aguilera, Francisco Javier (El Colegio de Chihuahua, 2021)
There is a growing demand for the use of digital information in present times. Thus, new challenges on cybersecurity like fending off attacks on vulnerabilities in current data storage systems. Industry 4.0 integrates technologies that handles private digital information, thus, the issues with cybersecurity are in the spotlight. The physical infrastructure—composed of: computers, routers, servers, switches, etc.—is one of the main aspects to consider. Its protection can be guaranteed through different means like the usage of biometric technologies to restrict access to a predetermined area, which is becoming crucial and stands out among other security techniques like the use of security guards, lockable doors, and those with electronic key access, etc. The application of digital image processing for facial and fingerprint recognition is presents throughout this work. Nonetheless, this chapter ends with two low-cost proposals to control access to a given area that take advantage of facial and fingerprint recognition authentication technology.